The Effectiveness Of Key Lime (Citrus Aurantifolia) And Slaked Lime (Calcium Hydroxide) In Reducing Stretch Marks In Postpartum Women - Lidia Widia; Ngestiningrum, Ayesha Hendriana; Ashriady, Ashriady (Politeknik Kesehatan Kemenkes Mamuju, 2025)
Key lime (Citrus aurantifolia) contains vitamin C and bioactive compounds that promote tissue repair and skin regeneration. The combination of key lime and slaked lime may help reduce stretch marks in postpartum women. Vitamin C in key lime and hydroxide compounds in slaked lime are thought to accelerate skin regeneration while exfoliating dead skin cells. This study aimed to analyze the effectiveness of the combination of key lime and slaked lime in reducing stretch marks among postpartum women. The research employed a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of twenty postpartum women (6 hours to 7 days after delivery) selected through purposive sampling, conducted from September to December 2024 at Paradise Mother and Child Hospital, Tanah Bumbu Regency. Inclusion and exclusion criteria were applied to determine eligible participants. The results of the study showed that the Sign Test yielded a p-value (Exact Sig. 2-tailed) of 0.002 (<0.05), indicating a significant effect of the treatment. Therefore, it can be concluded that the combination of key lime (Citrus aurantifolia) and slaked lime (calcium hydroxide) is effective in reducing stretch marks in postpartum women. It is recommended that this natural combination be used as an alternative treatment for postpartum stretch marks.